2 cases transformation myasthenia gravis to amyotrophic lateral sclerosis - A. G. Sanadze; L. F. Kasatkina (Нервно-мышечные болезни)
A72-year old woman and 38-year old man had clinical sings of myasthenia gravis with ptosis and double vision, speech, swallowing, face and limb weakness. They was diagnosed MG after tensilon test, responding to piridostigmine and prednisolon treatment, neuromusculardisorders and positive anti-AchR and titin antibodies. Four and 7 year ago after debut of myasthenia gravis they had clinical and electrophysiological symptoms of amyotrophic lateral sclerosis.